Resveratrol Attenuates Oxalate-Induced Renal Oxidative Injury and Calcium Oxalate Crystal Deposition by Regulating TFEB-Induced Autophagy Pathway - Wu, Yue; Xun, Yang; Zhang, Jiaqiao; Hu, Henglong; Qin, Baolong; Wang, Tao; Wang, Shaogang; Li, Cong; Lu, Yuchao (Frontiers in Cell and Developmental Biology, 2021)
The oxidative injury of renal tubular epithelial cells caused by inflammation and oxidative stress induced by hyperoxaluria is an important factor in the kidney calcium oxalate (CaOx) stone formation. Resveratrol (RSV) has been reported to reduce oxidative injury to renal tubular epithelial cells, and autophagy is critical for the protective effect of resveratrol. However, the protective mechanism of RSV in oxalate-induced oxidative injury of renal tubular cells and the role of autophagy in this process are still unclear. In our study, glyoxylic acid monohydrate-induced rats were treated with or without resveratrol, and it was detected that the overexpression of oxidant species, CaOx crystal deposition, apoptosis level, inflammatory cytokines and osteoblastic-associated protein expression were reversed by resveratrol. Additionally, Resveratrol pretreatment significantly reversed oxalate -induced decline in cell viability, cell damage, oxidant species overexpression, and osteogenic transformation in normal rat kidney epithelial-like (NRK-52E) cells. Furthermore, we found that RSV pretreatment promoted intracellular LC3Ⅱ upregulation, p62 downregulation, and autophagosome formation, whereas 3-methyladenine treatment reduced this effect. Moreover, RSV induced the expression of transcription factor EB (TFEB) in the nucleus of NRK-52E cells in a concentration-dependent manner. After transfection of NRK-52E cells with TFEB siRNA, we showed that the RSV-induced increase in TFEB expression and autophagosome formation were inhibited. Simultaneously, RSV-induced NRK-52E cells protection was partially reversed. These results suggested that RSV regulates oxalate-induced renal inflammation, oxidative injury, and CaOx crystal deposition in vitro and in vivo through the activation of a TFEB-induced autophagy.